Psychological and Pain Factors in Microsurgical Testicular Sperm Extraction (Micro-TESE) for Non-Obstructive Azoospermia: A Comparative Study of Successful and Unsuccessful Cases - AVCI , Ali Egemen; KENDİRCİ, Muammer and BASAR, Mehmet Murad (Urology Journal, 2024)
Purpose: This study aimed to assess postoperative pain, depression, and anxiety levels in infertile men who underwent microsurgical testicular sperm extraction (micro-TESE) for non-obstructive azoospermia (NOA) and compare results between patients with successful and unsuccessful sperm retrieval. Material and Methods: A total of 105 NOA patients participated, completing preoperative Beck Depression Inventory (BDI) and Situational and Transient Anxiety Inventory (SAI and TAI) questionnaires. Postoperatively, Visual Analog Scale (VAS) scores were recorded. Patients were categorized into primary and repeated micro- TESE groups, and scale scores, operation duration, and collected tubule count were compared. The relationship between micro-TESE outcomes, VAS scores, and additional analgesia needs was also examined. Results: Successful sperm retrieval was achieved in 55.9% of patients. While BDI, SAI, and TAI scores showed no significant intergroup differences, micro-TESE (-) patients exhibited significantly higher mean VAS scores (p < 0.001). VAS scores positively correlated with BDI score, operation duration, and tubule count, while patient age inversely correlated with micro-TESE results. Conclusion: Infertility, azoospermia, and unsuccessful sperm retrieval impact psychogenic status and pain levels in male patients. Additionally, a history of micro-TESE procedures and their outcomes elevate depression levels.